Accuracy of intraoperative identification of the tibial intercondylar eminence in the sagittal plane in dogs - Alcântara, Brenda M. [UNESP]; Minto, Bruno W. [UNESP]; Carrera, Alefe L. C. [UNESP]; Faustino, Rodrigo C. S. [UNESP]; Lopes, Lara C. M. [UNESP]; Dias, Luis G. G. G. [UNESP] (Wiley, 2025)
OBJECTIVE: To assess the accuracy of intraoperative identification of the tibial intercondylar eminence (TIcE) in the sagittal plane in dogs. STUDY DESIGN: Ex vivo experimental study. ANIMALS: A total of 20 stifles from 10 dogs (weight range: 20-30 kg; n = 20). METHODS: Stifles were positioned for a mediolateral radiographic projection with a hypodermic needle placed at the center of the medial collateral ligament (MCL) (C), immediately cranial (Cr), and caudal (Cd) to the ligament. Variables were assessed at the stifle flexions of 90° and 135° with both intact cranial cruciate ligament (CCL-In) and after mechanical transection (CCL-MT). Three evaluators measured the distance (d) between the TIcE and needle center. Statistical analysis involved a linear mixed model, with the Bonferroni test (p < .0125). RESULTS: Analyses of CCL-In and CCL-MT groups revealed statistically significant differences between needle positions and stifle flexion angles. In the CCL-In group, the C-90° position was closest to the stifle center (d = 0.45 ± 2.39). For the CCL-MT group, the C-135° position was nearest (d = 0.11 ± 2.18). CONCLUSION: The center of the MCL in the sagittal plane, at 135° of stifle flexion, served as a reliable anatomical reference for identifying the TIcE in dogs with CCL disease. CLINICAL SIGNIFICANCE: A meticulous intraoperative identification of the TIcE can improve the accuracy of tibial osteotomies, potentially optimizing tibial plateau leveling osteotomy outcomes.